2011
DOI: 10.1007/s11104-011-0851-6
|View full text |Cite
|
Sign up to set email alerts
|

Screening of rhizosphere bacteria from grapevine for their suppressive effect on Xiphinema index Thorne & Allen on in vitro grape plants

Abstract: Xiphinema index is the most aggressive root parasite affecting vines in Chile, controlled mainly chemically. The aim of this study was to identify rhizobacteria in grapevine roots growing in infested soils and to determine if some of these affect the parasitism caused by the nematode. Rhizobacteria of ungrafted grapevine cultivars from 11 vineyards were isolated using TSBA and identified with FAMEs analysis. The antagonistic effect to X. index of those from soils 1 to 4 was assessed in 500 ml pots treating 2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 38 publications
2
18
0
1
Order By: Relevance
“…Although Mediterranean Chile is one of the most important wine-producing regions and the area occupied by vineyards in Chile has rapidly expanded (Viers et al, 2013), there are very few studies exploring the microbial diversity of these vineyard soils (but see Aballay, Maternsson & Persson, 2011; Castañeda et al, 2015). Recently, Castañeda et al (2015) have shown that the soil bacterial communities in native forests and vineyards are similar, whereas the fungal communities differ between the habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Although Mediterranean Chile is one of the most important wine-producing regions and the area occupied by vineyards in Chile has rapidly expanded (Viers et al, 2013), there are very few studies exploring the microbial diversity of these vineyard soils (but see Aballay, Maternsson & Persson, 2011; Castañeda et al, 2015). Recently, Castañeda et al (2015) have shown that the soil bacterial communities in native forests and vineyards are similar, whereas the fungal communities differ between the habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, grape and derived products held an important economic role in the area, and this importance persists to the present day. Vineyards are extremely sensitive to phytopathogen attacks, and a huge interest has been devoted to understanding the mechanisms of virulence [1] and environmental-friendly biocontrol approaches [2]. Certain biocontrol strategies rely on the exploitation of beneficial traits of plant growth-promoting (PGP) microorganisms that are naturally associated with plants [3].…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained in this study indicate that rhizobacterial filtrates are able to produce in vitro mortality on X. index adults and juveniles and are in agreement with previous works (Aballay et al . ). Additionally, the results of the present work agree with other studies on intensively studied species, such as M. incognita (Jonathan et al .…”
Section: Discussionmentioning
confidence: 97%